Extended half‐life rFIX in major surgery—How to improve clinical practice: An intraindividual comparison - Valeri, Federica (Clin Case Rep, 2020)
Practical, safe, and effective hemostatic approach to orthopedic surgery using Extended Half‐Life factor IX in hemophilia B. By intraindividual comparison, we found a lower FIX consumption, number of infusions, and cost compared to plasma‐derived FIX.